Current and future experimental approaches in the study of grape and wine polyphenols interacting gut microbiota - Zorraquín, Irene; Sánchez‐Hernández, Eva; Ayuda‐Durán, Begoña; Silva, Mariana; González‐Paramás, Ana M; Santos‐Buelga, Celestino; Moreno‐Arribas, Maria V; Bartolomé, Begoña (Journal of the science of food and agriculture, 2020)
Interactions between polyphenols and gut microbiota are indeed a major issue of current interest in food science research. Knowledge in this subject is progressing as the experimental procedures and analysis techniques do. The aim of this article is to critically review the more leading‐edge approaches that have been applied so far in the study of the interactions between grape/wine polyphenols and gut microbiota. This is the case of in vitro dynamic gastrointestinal simulation models that try to mitigate the limitations of simple static models (batch culture fermentations). More complex approaches include the experimentation with animals (mice, rats, pigs, lambs and chicks) and nutritional intervention studies in humans. Main advantages and limitations as well as the most relevant findings achieved by each approach in the study of how grape/wine polyphenols can modulate the composition and/or functionality of gut microbiota, are detailed. Also, common findings obtained by the three approaches (in vitro, animal models and human nutritional interventions) such as the fact that the Firmicutes/Bacteroidetes ratio tends to decrease after the feed/intake/consumption of grape/wine polyphenols are highlighted. Additionally, a nematode (Caenorhabditis elegans) model, previously used for investigating the mechanisms of processes such as aging, neurodegeneration, oxidative stress and inflammation, is presented as an emerging approach for the study of polyphenols interacting gut microbiota. © 2020 Society of Chemical Industry